Pendekatan C-5 Sebagai Model Perintisan Gereja yang Efektif di Tengah Budaya Agama Mayoritas - Wahyudi Sri Wijayanto (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2025)
The obstacles for believers in conveying the Good News to the majority in Boyolal Regency, Central Java are the background for this research. This is interesting to study. Because of the wrong evangelical view that people who believe in Jesus must be Christians. Model C-5 (Church) church planting is church planting that does not change the identity of Christ's disciples. The aim of this research is to first look at the obstacles experienced by C-5 evangelists in Boyolali. Second, what is the C-5 model approach used in Boyolali. This research uses a qualitative approach with grounded theory study. The research results obtained were firstly evangelism with contextual Islamology. Second, family discipleship (silaturahmi or sinau). Third, teach students to make disciples.